2020
DOI: 10.1186/s12864-020-07226-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting genetic variation and positive selection followed the divergence of NBS-encoding genes in Asian and European pears

Abstract: Background The NBS disease-related gene family coordinates the inherent immune system in plants in response to pathogen infections. Previous studies have identified NBS-encoding genes in Pyrus bretschneideri (‘Dangshansuli’, an Asian pear) and Pyrus communis (‘Bartlett’, a European pear) genomes, but the patterns of genetic variation and selection pressure on these genes during pear domestication have remained unsolved. Results In this study, 338 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…These results suggest that NBS-LRR genes are distributed non-randomly across all chromosomes, showing a clustered distribution. The enrichment of NBS-LRRs in corresponding genomic regions suggested that the evolution of resistance genes may involve tandem duplications of linked gene families, as reported by previous studies [8,30].…”
Section: Chromosomal Distributions and Evolutionary Analysis Of Nbs-lrrssupporting
confidence: 79%
See 1 more Smart Citation
“…These results suggest that NBS-LRR genes are distributed non-randomly across all chromosomes, showing a clustered distribution. The enrichment of NBS-LRRs in corresponding genomic regions suggested that the evolution of resistance genes may involve tandem duplications of linked gene families, as reported by previous studies [8,30].…”
Section: Chromosomal Distributions and Evolutionary Analysis Of Nbs-lrrssupporting
confidence: 79%
“…Furthermore, only 33.8% of the NBS-LRRs were identified as orthologs between V. montana and V. fordii . Despite the similarity in genomic features between the two species [ 2 , 29 ], this discrepancy in NBS-LRR counts suggests that they might have undergone gene gains or losses to adapt to distinct environments [ 30 , 48 ]. This divergence might also explain the contrasting susceptibility of V. fordii to Fusarium wilt and the resistance of V. montana to this disease [ 3 , 4 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since then, many highly variable NLR gene loci that provide resistance to a variety of pathogens have been identified and isolated [11]. The release of high-throughput sequencing data enables genome-wide identification and analysis of NLR proteins [13,14] as well species-wide inventories of these proteins [8,15]. Release of the wheat reference genome (IWGSC RefSeq v1.0) [16] and mass resequencing data [17][18][19][20] have allowed us to identify the genome-wide repertoire of NLRs in wheat, determine their diversity in wheat relatives, and recover the diverse NLR gene pool through breeding and improvement of disease resistance in wheat.…”
Section: Introductionmentioning
confidence: 99%
“…NBS-LRR family genes are involved in the response of the plant’s innate immune system to pathogen infection and play an important role in defense against pathogens ( 39 ). The NBS-LRR family in seven pear varieties’ genomes was identified and classified into different subfamilies and integrated into PearMODB ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%